Penyebab Perempuan Menjadi Korban Kekerasan Akibat Minuman Keras di Lingkungan Keluarga - Sri Rizkhika; Lisnawaty W. Badu; Jufryanto Puluhulawa (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
This study aims to determine the causes of women becoming victims of violence due to alcohol in the family environment. The research method used is an empirical legal research method using a descriptive approach and qualitative analysis techniques. The results of this study indicate that there are two factors that cause women to become victims of violence due to drinking alcohol in Gorontalo City, namely internal factors consisting of the personality of the woman (victim) and the personality of the man (the perpetrator). While the external factors themselves consist of economic factors and infidelity factors. For victims, with the facts that occur in the field where alcohol is a trigger for domestic violence, it is for the victims, in this case the wife, to continue to provide awareness to her husband in order to place limits on the actions taken. And the perpetrators too so as not to exceed the limits of awareness in terms of drinking liquor so that families at home do not become victims of violence for actions due to excessive consumption of liquor.